The structural design and valence state control of cerium-based metal-organic frameworks for their highly efficient phosphate removal. (25th October 2021) - He, Jiaojie; Pei, Conghong; Yang, Yue; Lai, Bo; Sun, Yan; Yang, Liwei
Abstract: A series of cerium-based metal-organic frameworks (MOFs) with structural design and valence state modulation were fabricated for effective phosphate uptake, which were named as Ce-BDC-1, Ce-BDC-2 and Ce-BTC-1. The X-ray diffractometer (XRD) pattern revealed that Ce-BTC-1 was highly coordinatively unsaturated MOF. The Brunauer-Emmett-Teller analysis (BET) confirmed that Ce-BDC-1 possessed the largest specific surface area of 1285.57 m 2 /g, two-fold higher than the area of Ce-BTC-1 and thousand times larger than that of Ce-BDC-2. The result of X-ray photoelectron spectroscopy (XPS) demonstrated that the dominant valence state of cerium in Ce-BDC-2 was Ce (Ⅲ), while Ce-BDC-1 and Ce-BTC-1 were totally Ce (Ⅳ)-based materials. Impressively, although the physicochemical characteristics were quite divergent, Ce-BTC-1, Ce-BDC-1 and Ce-BDC-2 showed relatively close phosphate removal capacities (the maximum adsorption capacities of them were 242.0, 254.3 and 218.9 mg/g, respectively). Meanwhile, the variety of structure modification or valence state selection would in return affect their adsorption performances, leading to show their own advantage in different removal characteristics like fast adsorption speed, superb uptake capacity in solution with low or high concentration. This study provided three different strategies for preparing high-effective cerium-based adsorbents and revealed the relationship among physicochemical characteristics, adsorption mechanisms and adsorption performances, which might contribute to the design of new metal-based adsorbents. Graphical abstract: Image 1 Highlights: The cerium-based MOFs with structural and valence state design were fabricated. The maximum adsorption capacities of Ce-BTC-1, Ce-BDC-1 and Ce-BDC-2 were 242.0, 254.3 and 218.9 mg/g. Ce-BTC-1 was coordinatively unsaturated, showing enhanced phosphate removal under high concentration. Ce-BDC-1 possessed the largest specific surface area and fastest adsorption speed. Ce-BDC-2 with tervalence cerium exhibits great phosphate removal under low concentration.